The Implementation of the Ontario Language Curriculum 2023: Educator Initial Impressions - Jackson, Terri (Language and Literacy / Langue et littératie, 2025)
Effective implementation of a new curriculum requires investment in curriculum leaders, educator capacity-building, and resources. In their most recent curriculum releases, the Ontario Ministry of Education has failed to effectively support curriculum implementation (Office of the Auditor General for Ontario, 2020). Using a mixed-methods online survey, this study investigates the initial implementation of the Ontario Language Curriculum 2023 as perceived by Ontario educators. Research suggests that the Ministry of Education failed to adequately equip Ontario’s educators with professional development and resources in the initial implementation phase. Furthermore, it suggests strategies that can bolster implementation moving forward.